Characterization of the Migration of Bisphenol A and F Diglycidyl Ethers from Epoxy-coated Containers to Food Simulants. (11th February 2018) - Safta, Mehdi; Limam, Intissar; Bouajina, Amal; Ousji, Basma; Jomaa, Ghazi; Turki, Eya; Belgaied, Sayda; Driss, Mohamed Ridha; Kalfat, Rafik
ABSTRACT: This study evaluated the migration of bisphenol A diglycidyl ether (BADGE) and its chlorinated and hydrolyzed derivatives and bisphenol F diglycidyl ether (BFDGE) from the inner surface coatings of food containers into three food simulants including 3% (w/v) aqueous acetic acid, 10% (v/v) aqueous ethanol, and sunflower oil. After a storage period of 429 days from 155 to 584 days, BFDGE, a prohibited chemical by the European legislation, was not detected in any samples by high-performance liquid chromatography with fluorescence detection. However, BADGE, BADGE.H2 O, BADGE.HCl.H2 O, and BADGE.2H2 O were found at levels below the European Union limits. Conducted analyses using Fourier transform infrared spectroscopy in attenuated total reflectance mode showed that epoxy–phenolic lacquers may be used as food container coatings. Additional work using atomic force microscopy did not reveal the signs of degradation of the inner coatings in contact with the simulants.